PELATIHAN PENINGKATAN KINERJA USAHA UMKM PEREMPUAN DI JAKARTA DAN BANDUNG DI MASA PANDEMI COVID-19 - Penny Handayani; Benedicta Evienia; Brigitta Angie Petrawati; Geoffrey Kana Wirawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2023)
The Training for Women's MSME Business Performance Improvement in Jakarta and Bandung during the Covid-19 Pandemic has the following objectives: 1) Conduct community service based on the results of research that has been carried out with the title